Living the brand: brand orientation in the business-to-business sector - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2010)
Purpose - The purpose of this paper is to design and test a model for the internal anchorage of a business-to-business brand via corporate brand orientation. Design/methodology/approach - Data from 261 usable responses to a questionnaire distributed in the German business-to-business sector, were applied to model estimation by the soft modelling partial-least-squares regression technique. Findings - The structure of the brand orientation model is supported by the results. The findings demonstrate the positive influence of brand orientation on market and economic performance. Smaller business-to-business companies exhibit lower levels of brand orientation than larger counterparts, to their strategic disadvantage. Line of business and management type had no influence on brand orientation in this survey. Practical implications - Business-to-business brand managers now have empirically-based evidence for the benefits of intensive implementation of brand orientation. The associated four-level conceptual model of the phenomenon offers them an enhanced understanding of the process, procedures and probable outcomes. It can be used for management control as well as strategic planning and implementation. Originality/value - The paper is the first empirical study to examine the internal aspects of branding in the business-to-business sector, and one of the first large-scale surveys that is not industry-specific to analyse the link between brand management and company performance.
Keywords: Brands; Market orientation; Business-to-business marketing; Organizational culture; MARKET ORIENTATION; INDUSTRIAL; MODEL; CONSTRUCT; EQUITY